2011
DOI: 10.1038/nrmicro2602
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of host membranes by bacterial effectors

Abstract: Bacterial pathogens interact with host membranes to trigger a wide range of cellular processes during the course of infection. These processes include alterations to the dynamics between the plasma membrane and the actin cytoskeleton, and subversion of the membrane-associated pathways involved in vesicle trafficking. Such changes facilitate the entry and replication of the pathogen, and prevent its phagocytosis and degradation. In this Review, we describe the manipulation of host membranes by numerous bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
115
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 99 publications
0
115
0
Order By: Relevance
“…Although comprising less than 10% of total phospholipids, PIs are pivotal cellular regulators and play essential roles in a broad spectrum of cellular processes including defining intracellular organelle identity, cell signaling, proliferation, cytoskeleton organization, and membrane trafficking (9)(10)(11). Interference of the temporal and spatial distribution of intracellular PIs often leads to abnormal cellular functions, which has been capitalized by virulent invaders (12,13). Bacterial pathogens have evolved a variety of mechanisms to subvert PI metabolism in host cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although comprising less than 10% of total phospholipids, PIs are pivotal cellular regulators and play essential roles in a broad spectrum of cellular processes including defining intracellular organelle identity, cell signaling, proliferation, cytoskeleton organization, and membrane trafficking (9)(10)(11). Interference of the temporal and spatial distribution of intracellular PIs often leads to abnormal cellular functions, which has been capitalized by virulent invaders (12,13). Bacterial pathogens have evolved a variety of mechanisms to subvert PI metabolism in host cells.…”
mentioning
confidence: 99%
“…Modulation of host PI metabolism by Legionella is important for the establishment of the Legionella-containing vacuole (LCV) within which the bacterium replicates (8,12,13). It has been suggested that PI(4)P is enriched on the LCV membrane, which among other functions, anchors effectors such as SidM/DrrA, SidC, and SdcA to promote the recruitment and fusion of the endoplasmic reticulum derived vesicles with the LCV (18,19).…”
mentioning
confidence: 99%
“…In their active state, small GTPases interact with downstream effectors that promote membrane transport. Not surprisingly, many vacuolar pathogens regulate the recruitment and activation state of host cell GTPases to alter the trafficking of their vacuole [1,14]. Salmonella enterica Typhimurium initially recruits Rab5, a marker of early endosomes to its vacuole [15,16].…”
Section: Role Of Small Gtpases In Vacuole Stabilitymentioning
confidence: 99%
“…In common with many other intracellular pathogens, rickettsiae utilize a ''zipper'' mechanism to mediate their cellular internalization (Ham et al, 2011). Rickettsiae exploit the cytoskeleton to enter and spread within the host cell.…”
Section: Isolationmentioning
confidence: 99%